LITERASI MEDIA BERITA DAN LITERASI DIGITAL TERHADAP PARTISIPASI POLITIK ONLINE DAN OFFLINE - Sati, Lara (MediaKom : Jurnal Ilmiah Komunikasi, 2016)
Abstract: This research is motivated by the condition that the modern mass media technology has drastically changed the community. The skills and competence of media literacy and digital literacy are closely related to each other that is needed to live and work in a diverse community of media-information. Participation in the electoral process include more than just a voice. Political participation comes from freedom of speech, assembly and association, the ability to take part in the implementation of public affairs, and the opportunity to register as a candidate, campaigning, to have and to hold office at all levels of government. In this research, the data collected through experimentation methods quasi the non equivalent control group design. In quasi experimental pretest / posttest data were collected before and after the intervention (treatment). Comparison of the control group and the experimental group at the end of the study showed the effect of the experimental stimulus. The results of the analysis find that the news media literacy increasing the online and offline political participation, and the digital literacy increasing the online and offline political participation. Keywords: news media literacy, digital literacy, online and offline political participation